Is small beautiful? work-family tension, work conditions, and organizational size. - MacDermid, Shelley M.; Williams, Margaret; Marks, Stephen (Family Relations, 1994)
Part of a special section on work, stress, and families. A study was conducted to compare the links between work-family tension and work conditions in small and large workplaces. Interaction terms in a series of hierarchical regression analyses were used to test the hypothesis that work-family tension and work conditions would be stronger in small than in large workplaces. The findings indicated that women who reported more demanding jobs also reported more spillover from their jobs to their household responsibilities. Women who perceived benefits as more available and accessible reported less spillover from work to marriage, but only if they were employed in large workplaces. In addition, women who perceived greater closeness among coworkers were likely to report less spillover from work to marriage and to home management, but only if they were employed in small workplaces.